Color, texture, cooking properties and nutritional composition of extruded pasta incorporated with germinated horse gram (Macrotyloma uniflorum) flourc - *, Vandarkuzhali; Sangeetha, Narayanasamy (IJRDO-Journal of Applied Science, 2015)
Present study investigated the effect of germination of horse gram on the nutritional, physical and cooking characteristics of extruded pasta products. Horse gram seeds were germinated for 48 hrs at 20 ºC ± 2 ºC and subjected to drying in a force convention tray drier for 6 hrs at 50ºC. Germinated horse gram flour was mixed with refined flour and rice flour separately at 90%, 80% and 70% levels and pasta was prepared using single screw extruder at an extrusion temperature 40 ± 2 ºC with a pressure of 400 rpm. Physical parameters like pasting, color, texture and cooking characteristics were carried out to select best quality pasta. Extruded pasta with 70% germinated horse gram flour and 30% refined flour had minimum cooking loss with high firmness and low stickiness in texture profile. Based on this quality, pasta made with germinated horse gram flour and refined flour (70:30) was analysed for nutritional composition and sensory characteristics. Germinated horse gram flour as an ingredient in pasta composition significantly increased (p<0.05) the nutrients such as ash (1.73%), protein (28.99%), fiber (0.93%), vitamin C (3.09 mcg), calcium (27.92 mg) and phosphorus (386.43 mcg). Pasta cooked with 3 gm spice and vegetables scored higher values in sensory analysis. Hence, incorporation of germinated horse gram flour in pasta preparation enhanced the nutritional and sensory qualities of pasta with good acceptability which serve as a suitable food for all age group people.